The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/we.2555
|View full text |Cite
|
Sign up to set email alerts
|

Passive load alleviation on wind turbine blades from aeroelastically driven selectively compliant morphing

Abstract: Load alleviation control is highly desirable to reduce penalties associated with the added structural mass required to withstand rare load scenarios. This is particularly true for wind turbine designs incorporating long-span blades. Implementation of compliance-based morphing structures to modify the lift distribution passively has the potential to mitigate the impact of rare, but integrally threatening, loads on wind turbine blades while limiting the addition of actuation and sensing systems. We present a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Selective stiffness in compliant structures has previously been proposed as an alternative to bridge the gap between the trade-offs faced when designing morphing systems. 33,34 This type of stiffness variability can be achieved by exploiting local changes in compliant topologies. Several approaches to achieve local bistability within compliant structures have been explored in the literature, including leveraging thermally prestressed composite laminates, 19,[35][36][37] employing thin shells, 38,39 and utilizing bistable compliant mechanisms.…”
Section: Selective Stiffness and Shape Lock-in Effects From Geometric...mentioning
confidence: 99%
“…Selective stiffness in compliant structures has previously been proposed as an alternative to bridge the gap between the trade-offs faced when designing morphing systems. 33,34 This type of stiffness variability can be achieved by exploiting local changes in compliant topologies. Several approaches to achieve local bistability within compliant structures have been explored in the literature, including leveraging thermally prestressed composite laminates, 19,[35][36][37] employing thin shells, 38,39 and utilizing bistable compliant mechanisms.…”
Section: Selective Stiffness and Shape Lock-in Effects From Geometric...mentioning
confidence: 99%
“…Recent studies have shown that natural design strategies can be used to develop adaptive structures that automatically respond to external stimuli. These include but are not limited to dragonfly‐inspired flapping kites that adapt their stiffness in response to the wind speed, [ 16 ] Passive load alleviation of morphing structures for wind turbine blades, [ 17,18 ] passive morphing of a solar powered flying wing aircraft to enhance solar energy absorbency, [ 19 ] plant‐inspired composites that reconfigure upon immersion in water or change in the ambient humidity, [ 20,4 ] pollen‐inspired drug delivery capsules that collapse under pressure, [ 21,22 ] insect‐inspired artificial fliers that reversibly buckle upon collisions. [ 23–25 ] These studies have opened a new avenue to the design of a new generation of adaptive systems, which can emerge as an independent research area to be called as Mechanical Intelligence (MI).…”
Section: Figurementioning
confidence: 99%
“…However, this narrative has been challenged more recently, and instabilities have been exploited for novel functionalities. This has led to the creation of well-behaved nonlinear structures [5] such as shape-adaptive structures [6][7][8][9], deployable structures [10][11][12], zero or negative stiffness structures [13,14], energy harvesters [15], as well as non-destructive testing techniques [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%